Swarm of Mobile Robots for Security Surveillance Based on Android Smartphone and Firebase - Kurniawan, Afdhal; Gunawan, Alexander A. S.; Hartanto, Boby; Mili, Aditya; Budiharto, Widodo (International Journal of Intelligent Systems and Applications in Engineering, 2023)
A swarm of mobile robots is an approach used to coordinate large numbers of mobile robots for accomplishing specific tasks. This study utilizes swarm robots in a security surveillance scenario. The research involves the development of an affordable mobile robot based on an IOIO board. To enable its integration into swarm robot systems, the robot must be enhanced with communication capabilities, and an algorithm must be implemented to coordinate multiple robots. The robots should be able to communicate with each other both locally and online. An OpenWrt-based router is employed as the local network communication backbone. Firebase, a cloud based IoT database service, is also utilized as a platform for online communication. The design of the swarm robot system allows a user to monitor and assign tasks to the system remotely. Once connected to a local network, the swarm robots can operate and coordinate autonomously. The mobile robot should have a camera capable of identifying people and detecting motion, making it suitable for security surveillance applications. The experiments successfully demonstrated the swarm robot system's effectiveness in performing security surveillance tasks.